2006
DOI: 10.1167/iovs.05-1143
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor H Variant Y402H Is a Major Risk Determinant for Geographic Atrophy and Choroidal Neovascularization in Smokers and Nonsmokers

Abstract: The CFH Y402H variant is strongly associated with both GA and CNV in the U.K. population. This association is similar in smokers and nonsmokers. Heavier smokers with the CC genotype may be at particular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(87 citation statements)
references
References 18 publications
9
71
1
5
Order By: Relevance
“…Haplotype analysis showed that a SNP in the CFH gene that results in a tyrosine to histidine substitution at amino acid 402 in the Factor H protein can account for up to 50% of AMD cases in the human population, a number approaching 50,000,000 worldwide. Follow-up reports have since confirmed these findings in additional cohorts in the United States (212,223), Iceland (224), the United Kingdom (225), and France (226). Interestingly, the major CFH risk haplotype in the Japanese population appears to be different than that reported in other populations, although the protective haplotype is the same (227).…”
Section: Molecular Genetics Of Amd and Disease Associationsmentioning
confidence: 85%
“…Haplotype analysis showed that a SNP in the CFH gene that results in a tyrosine to histidine substitution at amino acid 402 in the Factor H protein can account for up to 50% of AMD cases in the human population, a number approaching 50,000,000 worldwide. Follow-up reports have since confirmed these findings in additional cohorts in the United States (212,223), Iceland (224), the United Kingdom (225), and France (226). Interestingly, the major CFH risk haplotype in the Japanese population appears to be different than that reported in other populations, although the protective haplotype is the same (227).…”
Section: Molecular Genetics Of Amd and Disease Associationsmentioning
confidence: 85%
“…16,17 A number of complement system proteins, complement activators and complement regulatory proteins were identified as molecular constituents of drusen, the hallmark extracellular deposits associated with early AMD 12,[39][40][41][42] and of geographic atrophy and choroidal neovascularization, the hallmark of advanced AMD. 43 Genetic studies revealed highly significant associations between AMD and variants of several complement pathway-associated genes, including complement factor H, complement factor H-related 1 and 3, complement factor B, complement component 2 and complement component 3. [39][40][41][42]44 Associations between markers of inflammation (such as C-reactive protein) and AMD have been observed in some 45,46 but not all 47 previous epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was found that variants in the CFH and LOC 387715 genes are the major genetic factors that predispose individuals to AMD. Although the allele frequency of CFH polymorphism varies among different populations (Grassi et al 2006;Li et al 2006;Conley et al 2006), and is not associated with AMD in the Japanese population (Gotoh et al 2006), many independent studies strongly suggest that it is an important etiological factor for both geographic atrophy and choroidal neovascularization (Sepp et al 2006). Polymorphism in the second major gene LOC 387715 is strongly associated with smokers (Schmidt et al 2006) although some studies did not find significant differences in risk allele frequency and smoking (Rivera et al 2005;Conley et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent genome scan studies have identified susceptibility loci on 1q, 3p, 6q, 9q and 10q (Barral et al 2006). Recently, several independent studies reported a strong association of the variant Y402H in the complement factor H (CFH) gene on 1q32, and the A69S variant in the LOC 387715 gene (on 10q26) as major risk factors predisposing individuals to both forms of AMD (Haines et al 2005;Klein et al 2005;Edwards et al 2005;Rivera et al 2005;Sepp et al 2006). In addition, a whole genome association study has identified a variant in the promoter region of the HTRA1 gene (on 10q26) that may also play a key role in AMD susceptibility Yang et al 2006).…”
Section: Introductionmentioning
confidence: 99%